Respiratory function of very prematurely born infants at follow up: influence of sex. Issue 3 (17th January 2006) - Thomas, M R; Marston, L; Rafferty, G F; Calvert, S; Marlow, N; Peacock, J L; Greenough, A
Abstract : Objective: To test the hypothesis that male compared with female prematurely born infants would have worse lung function at follow up. Design: Prospective follow up study. Setting: Tertiary neonatal intensive care units Patients: Seventy six infants, mean (SD) gestational age 26.4 (1.5) weeks, from the United Kingdom oscillation study. Interventions: Lung function measurements at a corrected age of 1 year. Main outcome measures: Airways resistance (Raw) and functional residual capacity (FRCpleth ) measured by whole body plethysmography, specific conductance (sGaw) calculated from Raw and FRCpleth, and FRC measured by a helium gas dilution technique (FRCHe ). Results: The 42 male infants differed significantly from the 34 female infants in having a lower birth weight for gestation, requiring more days of ventilation, and a greater proportion being oxygen dependent at 36 weeks postmenstrual age and discharge. Furthermore, mean Raw and FRCpleth were significantly higher and mean sGaw significantly lower. After adjustment for birth and current size differences, the sex differences in FRCpleth and sGaw were 15% and 26% respectively and remained significant. Conclusion: Lung function at follow up of prematurely born infants is influenced by sex.